Nano‐Sheets: Highly Integrated Organic–Inorganic Hybrid Architectures by Noncovalent Exfoliation of Graphite and Assembly with Zinc Oxide Nanoparticles (Adv. Mater. Interfaces 20/2016). Issue 20 (19th October 2016) - Marcia, Mario; Vinh, Chau; Dolle, Christian; Abellán, Gonzalo; Schönamsgruber, Jörg; Schunk, Torsten; Butz, Benjamin; Spiecker, Erdmann; Hauke, Frank; Hirsch, Andreas
Abstract : A supramolecular fully integrated nano‐architecture consisting of non‐covalently functionalized graphene and ZnO nanoparticles is prepared by Mario Marcia and co‐workers in article 1600365. By means of cationic water‐soluble perylene diimides, exfoliated 2D carbon nano‐sheets can be efficiently assembled together with anionic inorganic 0‐dimensional nanoparticles. These ultra‐thin nano‐films show an outstanding uniform thickness and high homogeneity in the centimetre‐scale.